Extrinsic Factors Influencing Fetal Deformations and Intrauterine Growth Restriction. (19th July 2012) - Moh, Wendy; Graham, John M.; Wadhawan, Isha; Sanchez-Lara, Pedro A.
Abstract : The causes of intrauterine growth restriction (IUGR) are multifactorial with both intrinsic and extrinsic influences. While many studies focus on the intrinsic pathological causes, the possible long-term consequences resulting from extrinsic intrauterine physiological constraints merit additional consideration and further investigation. Infants with IUGR can exhibit early symmetric or late asymmetric growth abnormality patterns depending on the fetal stage of development, of which the latter is most common occurring in 70–80% of growth-restricted infants. Deformation is the consequence of extrinsic biomechanical factors interfering with normal growth, functioning, or positioning of the fetus in utero, typically arising during late gestation. Biomechanical forces play a critical role in the normal morphogenesis of most tissues. The magnitude and direction of force impact the form of the developing fetus, with a specific tissue response depending on its pliability and stage of development. Major uterine constraining factors include primigravida, small maternal size, uterine malformation, uterine fibromata, early pelvic engagement of the fetal head, aberrant fetal position, oligohydramnios, and multifetal gestation. Corrective mechanical forces similar to those that gave rise to the deformation to reshape the deformed structures are often used and should take advantage of the rapid postnatal growth to correct form.